HUBUNGAN TINGKAT PENGETAHUAN REMAJA DENGAN PERILAKU SEKSUAL BERESIKO PADA SISWA KELAS IX DI SMP NEGERI 8 AMBON - Silvianovelista R Losoiyo; Priscilla Marcelina Thenu (Pasapua Health Journal, 2020)
Introduction: Adolescent sexual behavior is a multidimensional problem, influenced by various factors both within and outside the adolescent. adolescent or personal characteristics, family and factors outside the family such as school and the surrounding environment can predict adolescent sexual activity. Methods: this study uses a type of analytic survey research, with a cross-sectional study approach. The sampling technique used a total sampling of 66 respondents. Results: In this study, it was found that there was a relationship between adolescent knowledge and risky sexual behavior in class IX students at SMP Negeri 8 Ambon with a P value = 0.233. Conclusion: adolescent sexual behavior is at risk according to adolescent knowledge.